Program Hypnomathematics melalui Kata-Kata Positif untuk Guru SD 4 Bae, Kudus - Savitri Wanabuliandari; Ristiyani Ristiyani (Jurnal Pengabdian Pada Masyarakat, 2019)
TRAINING OF HYPNOMATHEMATICS THROUGH POSITIVE WORDS FOR TEACHERS AT SD 4 BAE. Mathematics is known as a subject that plays an important role in the world of education. Mathematics is also a basic knowledge that students must have in order to be able to continue to a higher level. Mathematics in elementary school is known as a subject that many students don't like and fear because it is considered difficult. The emergence of fear and difficult assumptions in mathematics due to the lack of students are motivated to learn Mathematics. From the results of the observations, it was found that teachers tended to be less attentive to students who were not active in mathematics, teachers also did not respond well when students had difficulty learning mathematics, teachers used negative words and were more inclined to frighten students who experienced difficulties in learning mathematics, and the teacher does not give a positive response to student success. Based on these problems, the purpose of these service is to provide training in hypnomathematics through positive words. Provide training in hypnomathematics through positive words that are able to improve teacher skills in motivating students to learn mathematics.The target of this service is to provide knowledge and training to teachers at SD 4 Bae about using hypnomathematics through positive words to motivate students.The method used in this service is interactive training and mentoring. As a result of this service, SD 4 Bae teachers were able to improve their skills in motivating student learning during mathematics learning.